Multidisciplinary training: The orbital model - Cavalheiro, C. A.; Soter de Silveira, P. C.; Gagliardi Palermo, P. C. (New Studies in Athletics, 2005)
Ever improving performance levels and the desire for competitive success have lead to the development of multidisciplinary approaches to preparing athletes. The idea is make specialist knowledge from a variety of fields and disciplines available to assist athletes in achieving their goals. Such an approach is not new and has been used by the medical profession for some time. However, when applied to athletes, the traditional models for managing such as system - the "Filter" model and the"Basic Support" model both have limitations related to the role of the coach. In an attempt to improve the working of such systems, the authors propose a new concept, which they call the "Orbital" model. It is based on the trajectory of an orbiting planet (the athlete), which is surrounded by satellites (professionals) and linked together by rings (coaches/trainers). This whole unit revolves around the sun (the performance goal or objective). Working with a number of high-level Brazilian athletes and in conjunction with the Brazilian Air Force Institute of Science in Physical Activity (Instituto de Ciências da Atividade Física da Aeronáutica - ICAF), the authors have developed a team along the lines of their concept and gain experience it is operation.